Video Scribe Learning Media Material Changes in Forms of Objects Solutions to Increase Competency in Natural Science Knowledge - Dewi, Ni Ketut Ratmita; Yudiana, Kadek (Jurnal Edutech Undiksha, 2023)
Students' low learning outcomes and enthusiasm in learning science are due to the content or material provided needing to be more interesting. Educators need to utilize technology, one of which is by using interesting learning media. This research aims to create VideoScribe learning media on material changing the shape of objects. This development research adapts the ADDIE development model. The data collection methods are interviews, observation, questionnaires, tests, and documentation. The data analysis techniques used are quantitative analysis and qualitative analysis. This research resulted in the validation of VideoScribe learning media on material changing the shape of objects, which was declared feasible from the validation results of learning material experts with a percentage (96.00%) with very good criteria. The validation results of learning media experts obtained a percentage (94.5%) with very good criteria. Both state that VideoScribe learning media is very suitable for use. The level of practicality of VideoScribe learning media from the results of teacher responses obtained a percentage (95.3%), and the results of student responses obtained a percentage (95.41%) with very practical criteria. Moreover, the level of effectiveness of VideoScribe learning media obtained an average pretest score (69.68) and an average post-test score (78.06). It was concluded that the VideoScribe learning media effectively improved student learning outcomes in the material on changes in the shape of objects for class V students.